A Revised Paradigm for Calculating the NPA Percentage in Banks - V.Vijaykumar, N.; Tripathi, Ankita (Indian Journal of Finance, 2022)
The gross and net NPA ratios are powerful indicators of the health of banks. Globally and more specifically in India, the increasing rate of non-performing assets has been a very critical issue for decades. Primarily, NPA ratios of banks indicate the quality of their rate-sensitive assets and are used by rating agencies, regulators, investors, and other stakeholders for decision-making ranging from distribution of dividends to classifying the banks under the prompt corrective action category. Since these ratios are pivotal, this study examined the existing system of calculation of these ratios and their lacunae. One of the objectives of this study was also to devise a new formula for the calculation of gross as well as net NPA percentages. A comparison of the net and gross NPA percentage in respect of a few banks as per the existing and proposed formula was done, and it was found that the difference was statistically significant. The study has important implications for the banking industry and may help the regulators and investors assess banks’ health more stringently than is presently being done.